2017
DOI: 10.1080/13607863.2017.1390732
|View full text |Cite
|
Sign up to set email alerts
|

Needs and quality of life of people with middle-stage dementia and their family carers from the European Actifcare study. When informal care alone may not suffice

Abstract: Objective: The Actifcare (Access to timely formal care) study investigated needs of people with dementia and their families during the phase in which formal care is being considered, and examined whether higher need levels are related to lower quality of life (QOL). Method: From eight European countries 451 people with dementia and their carers participated. Needs were measured with the Camberwell Assessment of Need for the Elderly. QOL was measured with the QOL-AD, and carer quality of life was measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 27 publications
(33 reference statements)
8
75
0
6
Order By: Relevance
“…Among this group, almost two-thirds reported many unmet needs (64.7%) [23]. Another study found that informal caregivers reported almost twice as many needs as the patients they care for [24]. Comprehensive identification of needs enables problem identification and adequate intervention that can eliminate or reduce the need.…”
Section: Discussionmentioning
confidence: 99%
“…Among this group, almost two-thirds reported many unmet needs (64.7%) [23]. Another study found that informal caregivers reported almost twice as many needs as the patients they care for [24]. Comprehensive identification of needs enables problem identification and adequate intervention that can eliminate or reduce the need.…”
Section: Discussionmentioning
confidence: 99%
“…Among this group, almost two-thirds reported many unmet needs (64.7%) [23]. Another study found that informal caregivers reported almost twice as many needs as the patients they care for [24]. Comprehensive identi cation of needs enables problem identi cation and adequate intervention that can eliminate or reduce the need.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, according to Europe-wide data, many citizens express a strong preference for informal care (in terms of the share of respondents stating that elderly parents are best cared for by their children, Eurobarometer survey, 2010). In addition, informal care is associated with a better quality of life, 16,17 may substantially reduce healthcare system costs through lower rates of hospital admissions 18,19 and safeguards households from the financial disaster that may arise when formal services are contracted. 20 Although cultural norms in favour of informal arrangements prevail in many countries, the increasing participation of women in the labour market, together with the lack of flexible working arrangements, among other circumstances, may generate considerable obstacles to the provision of LTC within the family.…”
Section: Long-term Care In Japan and Spain And Recent Cost Containmenmentioning
confidence: 99%